Bioethics in international law - Qasim Lafta, Lecturer, Dr. Hawra (The college of law and political science journal, 2023)
This research sheds light on the importance of bioethics and its conceptsWKDWLVEHLQJFRQIXVHGZLWKHWKLFVDQGSURIHVVLRQDOHWKLFV7KHUHVHDUFKFODULÀHVthe principles on which bioethics is based. The research problem was the scarcityof references related to the topic in question and the failure to address manyof the problems it raises, such as determining the conditions to be followed inFRQGXFWLQJ VFLHQWLÀF UHVHDUFK WKH PLQLPXP ULJKWV WKDW WKH SHUVRQ FRQFHUQHGwith protection must enjoy, and the obligations of states within the framework ofELRHWKLFV7KHVWXG\LVGLYLGHGLQWRWZRVHFWLRQV7KHÀUVWVHFWLRQGLVFXVVHGWKHGHÀQLWLRQRIELRHWKLFVZKLOHWKHVHFRQGVHFWLRQGLVFXVVHGWKH ULJKWVHQMR\HGE\the person concerned with protection in bioethics. The research is concluded witha set of results and recommendations. The most important of which are joininginternational agreements that deal with the subject under research, enactingappropriate legislation, and teaching it within the curriculum of medical colleges.